ANALYSIS OF ECONOMIC GROWTH RATE, HUMAN DEVELOPMENT INDEX, AND OPEN UNEMPLOYMENT RATE ON POVERTY RATE IN BANDUNG REGENCY 2011-2023 - Dani Rachman; Chanra Satria Putra (UPT Publikasi Ilmiah UNISBA, 2025)
This study investigates the impact of economic growth rate, human development index (HDI), and open unemployment rate on the poverty rate in Bandung Regency from 2011 to 2023. Using panel data regression analysis, the study examines how these macroeconomic variables influence poverty levels over time. The results show that economic growth and the unemployment rate do not have a statistically significant effect on poverty. However, HDI has a significant negative effect, suggesting that improvements in education, health services, and overall living conditions play a vital role in reducing poverty. These findings indicate that relying solely on economic growth or lowering unemployment may not be sufficient to address poverty effectively. Therefore, local governments should focus on integrated development strategies that prioritize investment in human capital, especially in education and healthcare sectors. Future research is recommended to explore additional social and regional factors that may affect poverty dynamics more comprehensively.